Tenogenic Cues Are Biochemically and Environmentally Distinct for Tendon Stem Cells and Mesenchymal/Stromal Stem Cells - Vera Citro; Marta Clerici; Giovanna Della Porta; Nicola Maffulli; Aldo R. Boccaccini; Tina P. Dale; Nicholas R. Forsyth (Stem Cells International)
Tendon tissue engineering draws on regenerative medicine principles, offering innovative solutions to address the challenges posed by tendon injuries and degenerative conditions. Tendons’ inherent limited regenerative capacity often hinders complete recovery from injuries, leading to chronic conditions and impaired functionality. Autologous mesenchymal/stromal stem cells (MSCs) and tendon-derived stem cells (TSCs), combined with growth factors (GFs) like GDF-5, GDF-6 and GDF-7, are emerging as potential therapies for tendinopathy. These GFs are crucial for tendon development and promoting tenogenic differentiation, though the exact pathways they activate remain unclear. For this reason, directly comparing all three pathways to assess their impact on both MSCs and TSCs is essential. This study examined the effects of GDF-5, GDF-6 and GDF-7 on tenogenic differentiation in MSCs and TSCs, with a focus on how oxygen levels (21% O2 vs. physoxia at 2% O2) influence this process. The expression profiles of key tenogenic genes (Scleraxis [Scx], Tenomodulin [Tnmd], Thrombospondin-4 [Thromb-4] and Tenascin-C [Tnc-C]) were explored by quantitative reverse transcription PCR (RT-qPCR) following supplementation with individual GFs. Transcriptional analysis was complemented by Tnmd immunofluorescence (IF) and image analysis to identify optimal differentiation parameters. The study highlighted GDF-7 as a powerful inducer of tenocyte-like cell differentiation in MSCs, showcasing sustained expression of tenogenic genes over time in 21% O2. Moreover, TSCs in physoxia differentiate into tenocytes without an additional GF requirement. In conclusion, the study lays a foundation for understanding the complex interplay of GFs, oxygen levels and cellular responses in the quest for tendon regeneration. In doing so, it establishes that different cell types have differing biochemical requirements for induction of tenogenic differentiation. While offering promising avenues for tissue engineering platforms, it underscores the need for further research to fully harness the potential of MSCs and TSCs in vivo for tendon regeneration.